The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1055/s-2000-3817
|View full text |Cite
|
Sign up to set email alerts
|

Bucrylate Treatment of Bleeding Gastric Varices: 12 Years' Experience

Abstract: The use of Bucrylate in emergency sclerotherapy achieved results in bleeding gastric varices on a par with those obtained in esophageal varices in cases of alcoholic and posthepatitis cirrhosis. The group of patients with portal hypertension due to prehepatic block (splenoportal thrombosis) showed no benefit from sclerotherapy in terms of obliteration of gastric varices, but benefited from elective surgery. The choice of the obliterating treatment indicated may be facilitated by classifying gastric varices int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
54
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 14 publications
(29 reference statements)
8
54
0
Order By: Relevance
“…Furthermore, we found that the incidence of bleeding from gastric varices in our patients is 22.7%, which is also similar to other reports [5] . In this study, the rate for primary hemostasis with NBC injection is consistent with the reported rate of 90% to 97% in other studies [8,14,16,[21][22][23] . In our study, sclerotherapy with 2 mL NBC diluted in 1 mL lipoidal was effective in control of bleeding in all our patients during the first 48 h.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we found that the incidence of bleeding from gastric varices in our patients is 22.7%, which is also similar to other reports [5] . In this study, the rate for primary hemostasis with NBC injection is consistent with the reported rate of 90% to 97% in other studies [8,14,16,[21][22][23] . In our study, sclerotherapy with 2 mL NBC diluted in 1 mL lipoidal was effective in control of bleeding in all our patients during the first 48 h.…”
Section: Discussionsupporting
confidence: 92%
“…Most reports on endoscopic treatment of bleeding gastric varices are small series, case reports, or retrospective reviews [14,15] . Not more than 1000 patients with bleeding GV have been treated with different sclerosing and coagulating agents.…”
Section: Introductionmentioning
confidence: 99%
“…Fundal varices, like GOV2 and IGV1 of Sarin classification, are known to be associated with a high-flow vessel originating in gastro-renal, gastrophrenic or cardiophrenic shunts, and this distinctive anatomy and physiology contributes to a more aggressive bleeding potential [17]. Kind et al reported similar rebleeding rates among GOV1 (19.6 %) and GOV2 (18.9 %) varices but higher rebleeding rate in IGV1 (66.5 %) [18]. However, in our series, that was not verified.…”
Section: Discussionmentioning
confidence: 99%
“…Kind et al reported that hospital mortality rate was 19.5 %, and it was associated to liver failure (76 % of cases) and hemorrhagic shock (8.8 %) [18]. In our study, factors that were associated with in-hospital mortality, were: poor hepatic function (Child-Pugh C), no immediate hemostasis with cyanoacrylate, need for Sengstaken-Blakemore tube after cyanoacrylate, presence of complications, very early rebleeding and prothrombin rate <42 %.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanoacrylate has been used widely in the management of bleeding gastric varices empirically and achieved a rather satisfactory hemostatic rate. 4 The rationale of using cyanoacrylates is to occlude large varices and eradicate varices rapidly. 5 Our results showed the superiority of cyanoacrylate injection over band ligation.…”
mentioning
confidence: 99%